Foreign Language Learning Management for World Class University Ranking (Comparative Study between State Islamic University (UIN) Sunan Kalijaga Yogyakarta and the University of Malaya (UM) Malaysia) - Widodo, Sembodo Ardi; Setiyawan, Agung; Zahida, Ana (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
The paper aims to compare the management of foreign language learning at UIN Sunan Kalijaga and the University of Malaya as a way to improve World Class University ranking for taking a closer look at the institutional management, institutional curriculum habit, learning strategies progress, and emerging problems for managing education solutions. The data were collected through interviews, observation, focus group discussions, and documentation. The research uses a qualitative method through interactive model analysis, content analysis, and comparative analysis. The research finds that UM has more focus on foreign language specialization, while UIN Sunan Kalijaga does not have a clear focus on language learning specialization. The foreign language learning at UM is intended for graduate programs. It aims to prepare the graduates with international language fluency for industrial purposes by wider choices of language programs and in-depth linguistic knowledge. Language learning strategies at Sunan Kalijaga UIN use active learning and interconnection-integration models, while UM uses Communicative Language Teaching. Learning problems occurring in UIN Suka are mostly caused by Human Recourses factors due to the lectures. Problems in UM occurs with students’ difficulty. Taking from the institutional aspects and foreign language curriculum, UM is more prepared in heading towards World Class University and globalization than UIN Sunan Kalijaga.